2023
DOI: 10.1017/s0954422423000124
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal muscle growth and protein turnover: a narrative review of current understanding

Abstract: A model explaining the dietary-protein driven post-natal skeletal muscle growth and protein turnover in the rat is updated, and the mechanisms involved described in this narrative review. Dietary protein controls both length and muscle growth which are interrelated through mechanotransduction mechanisms with muscle growth induced by both stretching subsequent to bone length growth and from internal work against gravity. This induces satellite cell activation, myogenesis and remodeling of the extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 336 publications
0
4
0
Order By: Relevance
“…Thus, the existent of an upper limit to post-prandial protein deposition in both children and adults can be considered firmly established by the phenomenology of both childhood growth to adulthood and studies of healthy adult populations and their dietary protein intakes discussed above. Clearly although information is emerging on the mechanisms involved in such limitation of post-prandial protein deposition from both animal and human studies especially of MPS (42,44,120) , much remains to be revealed. The studies of leucine oxidation in response to feeding increasing protein intakes (105,106) suggest that utilisation was falling at the higher intakes fed in these subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the existent of an upper limit to post-prandial protein deposition in both children and adults can be considered firmly established by the phenomenology of both childhood growth to adulthood and studies of healthy adult populations and their dietary protein intakes discussed above. Clearly although information is emerging on the mechanisms involved in such limitation of post-prandial protein deposition from both animal and human studies especially of MPS (42,44,120) , much remains to be revealed. The studies of leucine oxidation in response to feeding increasing protein intakes (105,106) suggest that utilisation was falling at the higher intakes fed in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The key feature of the protein-stat concept is the interaction between bone length growth and appendicular muscle mass, whereby a phenotypical specific capacity for muscle growth is established through mechanotransduction mechanisms. Thus, the diurnal cycle of post-absorptive losses and post-prandial gains will occur to maintain muscle mass at the maximum, phenotypically controlled level, at which further protein deposition in muscle is limited by a 'bag full' signal (42)(43)(44) . Any additional protein intake above the habitual level can be deposited within the splanchnic tissues to a limited extent and will then be diverted to lipogenesis and adipose tissue expansion.…”
Section: Post-prandial Protein Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle mass is regulated by the balance between protein synthesis and degradation[ 6 , 7 ], and is governed by anabolic hormones, such as insulin-like growth factor (IGF)-1, and catabolic hormones, such as glucocorticoids[ 8 , 9 , 10 ]. For example, IGF-1 treatment promotes hypertrophy of C2C12 myotubes[ 11 ] and proliferation of chick embryonic myoblasts[ 12 ].…”
Section: Introductionmentioning
confidence: 99%